Just Medicare : What's In, What's Out, How We Decide - Flood, Colleen M. (Colleen Marion), 1966- (Book collections on Project MUSE., 2006)
The most important issue facing Canadian health care today is access to services. But who decides what services will be publicly funded, and how? The essays in Just Medicare explore the diverse means by which law influences what should and should not be covered by publicly-funded Medicare. Edited by Colleen M. Flood, the collection demonstrates three analytical approaches to the question of what services attract public funding. The first describes the existing processes for determining what is in and out of the publicly-funded sector and what is left to the private sector. The second approach suggests the principles that should guide decision-making and then investigates existing decision-making processes to see whether or not such principles are applied. The third analytical approach focuses on the processes of determining what services are publicly funded and, in particular, the right to review or appeal those decisions. The role of law is usually underestimated by those in health policy. Just Medicare illustrates that legal scholars can also contribute to the issue of how to allocate scarce health resources by determining what constitutes fair processes for decision-making, and by challenging unjust processes. In re-evaluating the potential of the law, this collection adds an important new dimension to the issue of health care in Canada.